1173The impact of adverse and positive experiences on inflammatory outcomes in Australian and UK children. (2nd September 2021) - Guo, Shuaijun; Gondek, Dawid; O'Connor, Meredith; Cahill, Stephanie; Downes, Marnie; Moreno-Betancur, Margarita; Burgner, David; Slopen, Natalie; Goldfeld, Sharon; Wake, Melissa; Juonala, Markus; Kerr, Jessica; et al.
Abstract: Background: Inflammation is one of key mechanisms linking childhood experiences to later chronic disease risk. Childhood adversity is associated with inflammation, but little is known about positive experiences. We examine how adverse and positive experiences are associated with inflammatory markers in late childhood, and whether they have an interaction effect. Methods: Data sources: Longitudinal Study of Australian Children (LSAC; N = 1237) and Avon Longitudinal Study of Parents and Children (ALSPAC; N = 3488). Exposures: Adverse and positive experiences assessed from 0 to 11 (LSAC) and 0-14 years (ALSPAC). Adversity indicators included parent legal problems, family violence, mental illness, substance abuse, harsh parenting, parental divorce, neighbourhood violence, family member death, and bullying victimization. Positive experiences included positive parenting practice, trusting and supportive relationships, supportive neighbourhood and home learning environments, social engagement and enjoyment. Outcomes: Inﬂammation quantiﬁed by high-sensitivity C-reactive protein (hsCRP) and glycoprotein acetyls (GlycA). Analyses: Linear regression was used to estimate relative change in inﬂammatory markers, adjusted for sociodemographics. Outcomes were log-transformed. Results: Exposure to adversity was associated with higher levels of inﬂammation (e.g., CRP: β = 8.8%, 95% CI= -16.5% to 34.2% in LSAC), whereas exposure to positive experiences was associated with lower levels (e.g., CRP: β=-18.9%, 95% CI= -45.8% to 7.9% in LSAC), after adjusting for sociodemographics. There was no interaction effect of adverse and positive experiences on inflammation. Conclusions: Adverse and positive experiences have independent and small effects on children's inflammation across two cohorts. Key messages: Positive experiences are critical to inform interventions to improve inflammatory outcomes for children who face adversity.